Scar after Intradermal Mattress versus Subcuticular Continuous Sutures: A comparative study - Manandhar, Krishna (Journal of Society of Surgeons of Nepal, 2021)
Introduction: Subcuticular continuous technique and buried mattress suture produce good results. The study compared results following these techniques using POSAS. Methods: Patients were enrolled on out-patient basis and grouped into I for Intradermal Buried Vertical Mattress Suture (IBVMST) and II for Subcutaneous Continuous with absorbable suture techniques (SCAST) and followed up to six months. Suture time, number of sutures and POSAS items were evaluated, correlated and analyzed. Results: Included were 63 patients. No significant difference was noted in Total OSAS as well as in Overall Opinion Scores between both groups, although group I scars were significantly better in relief and pliability, with p value of 0.019 and 0.018, respectively. In group I, category 1-2cm wounds needed more repair time; significant correlation was found between number of stitches and total POSAS; surface area and vascularity were significantly related with Observer Opinion and more scars were smooth, flexible, thinner and less vascular. In group II, category >5cm wounds needed more closure time; surface area was significantly related to Observer Opinion and scars were less expanded. In both groups, colour was significantly correlated with Patient Opinion. Total POSAS difference between the two groups was insignificant 0.9305, indicating no technique was superior, despite favourable group I results. Conclusion: No group was superior but revealed differences. The scars from IBVMST were favoured by observer opinions while scars from SCAST by patient opinions. More of IBVMST scars were smooth, flexible, thinner and less vascular but more of SCAST scars were less expanded. Lastly, short wounds closure are quicker with IBVMST while long wounds closure are quicker with SCAST.